Time dependent creep response of ultra-high-performance concrete without fiber reinforcing - Rogowski, Ryan C. (Kansas State University, 2022)
With increased usage among today’s modern infrastructure, ultra-high-performance concrete (UHPC) and its mechanical properties have been the focus of many research projects and experiments. Understanding the advantages of this relatively new material can provide immense benefits in design of global infrastructure. The purpose of this study is to fill the gaps in understanding of long-term deformation behavior and structural significance of UHPC mixtures by accurately measuring and modeling the creep strain observed in UHPC specimens. For this study, a series of six, 2.5” by 2.5” by 36” column specimens were tested, three cast with normal strength concrete and three cast with a modified ultra-high-performance concrete without steel fibers. The specimens were loaded to varying stress levels defined as fractions of measured f’c values for a duration of 28 days. Displacement measurements were taken at predetermined time intervals using a Whittemore gauge and embedded brass inserts. The data collected for each specimen was fitted using a Laplace Transform Elastic-Viscoelastic solution. The fitted data was then used to show and compare calculated values of creep compliance and creep coefficients for the various stress levels of each concrete mix. The creep compliance values after 28 days for the normal strength concrete ranged from 2.48E-07 to 3.05E-07 psi⁻¹ and the 28-day creep coefficients ranged from 0.27 to 1.69. The creep compliance values after 28 days for the modified ultra-high-performance concrete ranged from 2.08E-07 to 2.21E-07 psi⁻¹ and the 28-day creep coefficients ranged from 0.38 to 0.50. The best fit models for creep, shrinkage and recovery curves and their respective fit parameters are presented as well.
Keywords: UHPC; Creep; Concrete; Shrinkage; Recovery